2017
DOI: 10.1111/jcmm.13311
|View full text |Cite
|
Sign up to set email alerts
|

Ectodysplasin A regulates epithelial barrier function through sonic hedgehog signalling pathway

Abstract: Ectodysplasin A (Eda), a member of the tumour necrosis factor superfamily, plays an important role in ectodermal organ development. An EDA mutation underlies the most common of ectodermal dysplasias, that is X‐linked hypohidrotic ectodermal dysplasia (XLHED) in humans. Even though it lacks a developmental function, the role of Eda during the postnatal stage remains elusive. In this study, we found tight junctional proteins ZO‐1 and claudin‐1 expression is largely reduced in epidermal, corneal and lung epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 41 publications
(52 reference statements)
0
14
0
Order By: Relevance
“…EDA is a cytokine and part of the tumor necrosis factor family that functions in ectodermal organ development. In adulthood it is expressed in the kidney, and it functions to promote epithelial barrier function ( 52 ). EDA was reported to be significantly lower in peripheral blood mononuclear cells of CKD and end-stage renal disease subjects ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…EDA is a cytokine and part of the tumor necrosis factor family that functions in ectodermal organ development. In adulthood it is expressed in the kidney, and it functions to promote epithelial barrier function ( 52 ). EDA was reported to be significantly lower in peripheral blood mononuclear cells of CKD and end-stage renal disease subjects ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that corneal epithelium is in an active wound-healing process 18 h after abrasion (Kalha et al, 2018b). Moreover, it was shown that Eda −/− animals present high corneal dystrophy, along with impaired corneal epithelium barrier function and delayed cornea wound healing (Li et al, 2018(Li et al, , 2017Wang et al, 2016). Our Eda −/− mouse strain did not exhibit corneal dystrophy in young animals (13 wo), but an epithelial thinning in old ones (52-64 wo) (Fig.…”
Section: Eda Loss Of Function Results In Impaired Lg Maturationmentioning
confidence: 53%
“…The Eda gene regulates the morphogenesis of various ectodermal structures such as hair, teeth, nails, and exocrine glands, and when mutated, is responsible for X-linked hypohidrotic ectodermal dysplasia in humans. In Eda mutant Tabby mice, tight-junction proteins such as Zonula Occludens-1 (ZO-1) and Claudin-1 were dramatically downregulated, resulting in epithelial barrier dysfunction in various tissues including the cornea [ 53 ]. Furthermore, it was shown that EDA promotes corneal epithelial barrier homeostasis via the activation of Hedgehog signaling, which results in an increased production of ZO-1 and claudin-1 [ 53 ].…”
Section: Current Evidence Of Hedgehog Pathway Involvement In Physiolo...mentioning
confidence: 99%